THE EFFECT OF COMPENSATION, WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PRODUCTIVITY IN THE SERVICE PEKANBARU CITY MSME COOPERATIVE - Hendri Arulan; Ibnu Ramadhan Imanuullah; Sabri (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this study was to determine the effect of compensation on employee productivity at the Department of Cooperatives of UMKM in Pekanbaru City. To determine the effect of motivation on employee productivity at the Department of Cooperatives of SMEs in Pekanbaru. This study aims to determine the effect of compensation, work discipline and motivation on employee productivity at the Pekanbaru City UMKM Cooperative Service. The method in this study using a quantitative approach. The data analysis technique in this study used the classical assumption test, multiple linear regression, hypothesis testing (t test and F test), and the coefficient of determination. Based on the results of the study, it showed that the partial compensation had a significant effect on the employees of the Pekanbaru City UMKM Cooperative Service. The results of this study indicate that work discipline has a significant effect on employees of the Pekanbaru City UMKM Cooperative Office. The results of this study indicate that motivation partially has a significant effect on employees of the Pekanbaru City UMKM Cooperative Service. Based on the results of this study, compensation, work discipline and motivation simultaneously affect employee productivity at the Department of Cooperatives of UMKM in Pekanbaru City.